ARTIFICIAL INTELLIGENCE IN SCIENCE LEARNING IN PRIMARY SCHOOLS - Suttrisno, Suttrisno; Yulia, Nurul Mahruzah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Ease of access to information is both an advantage and a challenge for today's young generation. Students who are faced with easy access to information must be able to analyze and filter the information they receive from an early age. The development of this technology also needs to be balanced with efforts to develop Indonesian human resources. Through the independent curriculum, it is hoped that the quality of Indonesian human resources will be higher. The Merdeka Curriculum has an essential difference by combining science and social studies at the elementary school level to become science. In this research, science subjects were collaborated with a technology-based learning model using Artificial Intelligence, with the aim of describing students' abilities when taking part in the learning. This research was conducted using a descriptive qualitative approach. Four data collection techniques were used to describe this research, including interviews, observation, questionnaires, and documentation. The results of this research show that science and science learning in elementary schools using Artificial Intelligence is very interesting for students with 95% indicators of learning interest. The use of Artificial Intelligence also trains students in accessing information and being more careful in sorting information. A finding that is no less interesting is that in the Artificial Intelligence learning process, there needs to be special and specific guidelines, so that students can achieve the Learning Goals efficiently.